Spinel Harzburgite-Derived Silicate Melts Forming Sulfide-Bearing Orthopyroxenite in the Lithosphere. Part 1: Partition Coefficients and Volatile Evolution Accompanying Fluid- and Redox-Induced Sulfide Formation - Bénard, A.; Le Losq, C.; Müntener, O.; Robyr, M.; Nebel, O.; Arculus, R. J.; Ionov, D. A. (Frontiers in Earth Science, 2022)
We report abundances of major, trace and volatile elements in an orthopyroxenite vein cutting a sub-arc, mantle-derived, spinel harzburgite xenolith from Kamchatka. The orthopyroxenite contains abundant sulfides and is characterised by the presence of glass (formerly melt) both interstitially and as inclusions in minerals, comparable with similar veins from the West Bismarck arc. The glass formed by quenching of residual melts following crystallisation of abundant orthopyroxene, amphibole and minor olivine and spinel. The interstitial glass has a low-Ti, high-Mg# andesite composition, with a wide range of H2O and S contents but more limited F and Cl variations. We calculate trace element partition coefficients using mineral and glass data, including those for halogens in amphibole, which agree with experimental results from the literature. Despite having a similar, high-Mg# andesite composition, the orthopyroxene-hosted glass inclusions usually contain much more H2O and S than the interstitial glass (4-7 wt% and ~2600 ppm respectively). The initial vein-forming melts were oxidised, recording oxygen fugacity (fO2) conditions up to ~1.5 log units above the fayalite-magnetite-quartz (FMQ) oxygen buffer. They intruded the sub-arc mantle lithosphere at ≥1300°C, where they partially crystallised to form high-Mg# andesitic derivative melts at ca. 1050-1100°C. Comparison with literature data on glass-free orthopyroxenite veins from Kamchatka and the glass-bearing ones from West Bismarck reveal fundamental similarities indicating common parental melts, which were originally produced by low-degree melting (≤5%) of spinel harzburgite at ≥1360°C and ≤1.5 GPa. This harzburgite source likely contained ≤0.05 wt% H2O and a few ppm of halogens. Volatile evolution inferred from glass compositions shows that: (i) redox exchange between S6+ in the original melt and Fe2+ in the host mantle minerals; together with (ii), the formation of a S-bearing, (H2O, Cl)-rich hydrothermal fluid from the original melt, provide the conditions for the formation of abundant sulfides in the orthopyroxenites during cooling. During this process, up to 85% of the original melt S content (~2600 ppm) is locally precipitated as magmatic and hydrothermal sulfides. As such, melts derived from spinel harzburgite sources can concentrate chalcophile and highly-siderophile metals in orthopyroxenite dykes and sills in the lithosphere.